math
rewrite the equation so that y is a function of x.then use the result to find y when x= 2,1,0,1 6x2y=10
asked by
brittney

i meant 6x2y=10
posted by brittney
Respond to this Question
Similar Questions

math
rewrite the equation so that y is a function of x.then use the result to find y when x= 2,1,0,1 6x1=4y+2 
math
rewrite the equation so that y is a function of x.then use the result to find y when x= 2,1,0,1 2y3x16=0 
math
Rewrite the equation so that y is a function of x: 1. 2/3y+4=2x 2. 1/2(y+5)+4x=3x 3. Use the result in Ex. 1 to find y when x= 1, 0, and 2. 4. Use the result in Ex. 2 to find y when x= 1, 0, and 2. Thank you very much for any 
math
Rewrite the equation so that y is a function of x: 1. 1/2(y+5)+4x=3x 2. Use the result in Ex. 1 to find y when x= 1, 0, and 2 __________ Can you please check if this is right? 1. y=2x+4.5 2. f(1)=2(1)+4.5 =6.5 f(0)=2(0)+4.5 
algebra 116
Rewrite the equation y = 5x – 2 as a function of x. This problem is already a function of x. y = 5x  2 as a function of x. Rewrite the equation –x – 4y = 20 as a function of x. Graph f(x) = –3x – 2. Solve the system by 
math
rewrite each equation as afunction of x.3y+4y=11 Where are the equations? rewrite this equation as a function of x.3y+4y=11 y=x 
Math
The graph of a quadratic function has vertex(3,4) and passes through the point (4,1). Find the equation of the function in standard form. Rewrite the equation in general form. Could someone explain to me how to do this, just 
Math
The graph of a quadratic function has vertex(3,4) and passes through the point (4,1). Find the equation of the function in standard form. Rewrite the equation in general form. Could someone explain to me how to do this, just 
Math
How would you rewrite the equation y = 3x+1 as a function of x. Hmmm. It is written now as a function of x. Do you mean like this, where x is a function of y? x= 1/3 y 1 ? Could this be a trick question? I thought It was already 
matg
transform function f(x)=x^2 into a new function g(x) by shifting f(x)horizontally 9units to the rig t, reflecting the result across the x axis, and then shifting the result up 4 units. find the equation g(x)